RETENSI VITAMIN A PADA MINYAK GORENG CURAH YANG DIFORTIFIKASI VITAMIN A DAN PRODUK GORENGANNYA [Retention of Vitamin A in Vitamin A-Fortified Bulk Palm Oil and the Products Fried in the Oil] - Drajat Martianto; Sri Anna Marliyati; Aini Aqsa Arafah (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2009)
Susenas data shows that almost 100 % of the Indonesian people consume cooking oil regularly with an average per capita consumption of more than 20 gram/day. Palm oil is a dominant cooking oil in Indonesian market.Approximately 70 % of palm oil is sold bulk in the market, which is commonly called as ‘minyak curah’. Previous studies recommended that cooking oil, particularly the bulk palm oil, should be used as the vehicle in vitamin A fortification. The objective of the study was to evaluate the retention of vitamin A in foods that were fried using the fortified bulk palm oil. The selected food products were the most frequently consumed food by school children in Barranglompo Island, Makassar City, i.e of roti lasuna, roti kambu, jalangkote, and ikan kembung como goreng. The study showed that the retention of vitamin A significantly decreased with increasing number of frying repetition, but in general, the loss of vitamin A was less than 50% after the third frying. The retention of vitamin A after the first, second and third frying wasin range of 81-94%, 64-77%, and 51-63% respectively.